2011
DOI: 10.1016/j.bbi.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of indoleamine 2,3-dioxygenase polymorphisms with interferon-alpha-related depression in hepatitis C

Abstract: Our results suggest no influence of the variants in the IDO gene and the diagnosis of interferon-α-related depression in the Brazilian population. Interferon-α-related depression may impose persistent psychopathology on at least 15% of the depressed patients even 2 years after antiviral therapy termination. The cross-sectional design is a limitation of our study, predisposing memory bias. Prospective pharmacogenetic studies are warranted to continue investigation of the impact of IDO polymorphisms on the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…In presented paper the both studied polymorphisms of IDO1, i.e., c.-1849C > A (rs3824259) and c.-1493G > C (rs10089084), are localized in 5 region of the gene. A previous study showed no association between the two polymorphisms and IFN-α-related depression [61]. Similarly, our team found no correlation between the frequency of the c.-1849C > A (rs3824259) polymorphism and the risk of stroke occurrence.…”
Section: Discussionsupporting
confidence: 51%
“…In presented paper the both studied polymorphisms of IDO1, i.e., c.-1849C > A (rs3824259) and c.-1493G > C (rs10089084), are localized in 5 region of the gene. A previous study showed no association between the two polymorphisms and IFN-α-related depression [61]. Similarly, our team found no correlation between the frequency of the c.-1849C > A (rs3824259) polymorphism and the risk of stroke occurrence.…”
Section: Discussionsupporting
confidence: 51%
“…Patients who carried the C/C genotype were more likely to exhibit moderate or severe depression at week 12 of IFN-α treatment compared with those with either the C/T or T/T genotypes (Smith et al , 2011). However, a second cross-sectional study, conducted in a Brazilian population, found no associations (Galvao-de Almeida et al , 2011). Utilizing the STAR*D cohort, Cutler et al (2012) discovered two IDO SNPs (rs2929115 and rs2929116) that were associated with response to treatment with citalopram.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the genes involved with KYN pathway may play an important role in both pathogenesis and treatment of mood disorders. However, in patients with IFN-α therapy depression and anxiety the symptoms were not linked to variants in the IDO gene (Galvao de Almeida et al, 2011), though these discrepancies could be related to the cross-sectional study design.…”
Section: Resultsmentioning
confidence: 99%